Fishery legislative reform towards Japan’s Fukushima nuclear wastewater discharge into the sea—A Chinese perspective - Meng Li (Frontiers in Marine Science, 2023)
Japan’s discharge of Fukushima nuclear wastewater into the sea will have a profound and far-reaching impact on the marine environment and the fishing industry. Although Japan did not discharge nuclear wastewater directly into China’s waters, the wastewater flowed into the sea and infringed upon China’s rights and interests in pelagic fishing, as the nuclear-contaminated water is fundamentally different from discharges from normal nuclear plants. After the People’s Republic of China was founded, the Central Government and people’s governments of all levels started to manage fishery. However, the fishery management measures at this stage were primarily targeted the fishing industry itself, particularly the marine fishing industry. Several problems of China’s existing fishery legislation do not cope effectively with Japan’s nuclear sewage discharge. China’s fishery legislation keeps pace with the development pace of international laws, but it has not enacted specific regulations on certain types of marine pollution, such as nuclear sewage pollution. The Fisheries Law of the People’s Republic of China needs to produce an extraterritorial effect indirectly through other laws and regulations. China’s existing domestic laws only stipulate the rights of coastal countries. In this context, China’s fishery legislature should find a way forward, including changes in management standards; facilitating the formation of a complete extraterritorial effect by China’s fishery legislation a complete extraterritorial effect; improving supporting administrative legislation system; and facilitating the digitalization of fishing management to monitor Japan’s nuclear sewage discharge and its resultant harm, etc.